(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Despite being foreseen by the Italian Constitution, as of today, the right to social assistance has not been enforced yet, supposedly due to administrative and economic hindrances that still persist. A main attempt to move forward the effectiveness of right to social assistance has been carried out in 2000 with a general reform of the social care sector. However, the successive constitutional law nr. 3 of 2001 has vanished the overall sense and the potential impact of that reform, leaving the right to social assistance in a kind of legal limbo, i.e. suspended between its formal claim and its material indeterminateness. Hereafter is an attempt to retrace the recent evolution of this right, along with a critical analysis of the reasons that presumably induced the legislators to disregard its enforcement. In addition, several suggestions emerged in the debate about the attainability of the right to social assistance are included and examined.